THE INFLUENCE OF WORKPLACE SPIRITUALITY AND WORKPLACE CLIMATE ON EMPLOYEE PERFORMANCE - M Hibbul Watoni; Joko Suyono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The objective of this study was to determine the influence of workplace spirituality and workplace climate on employee performance in Sharia Banks in East Kalimantan Province. The samples in this study were 160 employees of the marketing division, using the probability sampling technique and the method used was stratified random sampling. The type of data used was in the form of cross-sectional data, while the source of the data used was primary data. The data collection method used a questionnaire, using a scale of one to five (Likert scale) that has been tested previously by testing the validity and reliability. The data analysis technique used multiple linear regression analysis, t test, f test, and determination test. Based on data analysis using SPSS 20 for windows, it can be concluded that the partial and simultaneous tests of workplace spirituality and workplace climate have an influence on the employee performance inSharia Banks in East Kalimantan Province.